Youth economy, crisis, and reinvention in twenty-first-century China : morning sun in the tiny times - Xiao, Hui Faye (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book surveys the explosive youth culture in twenty-first century China, an active and powerful force catalysing cultural innovations, social changes, and collective efforts, re-inventing a pluralistic and multivalent youth (qingnian) in an age of enormous change, division and uncertainty. Providing a comprehensive analysis of literary, cinematic, musical, televisual, and social media representations about, for and by disparate youth groups, this book seeks to offer a systematic investigation of a trans-medial and multi-locale youth culture. In so doing, it examines contributions from high school dropouts, industrial migrant workers and "leftover women", as well as best-selling writers and filmmakers, cultural entrepreneurs and young feminist activists. Observing the Chinese youths' deployment of "small" genres, such as light novels and short videos, in addition to digital media, this book ultimately demonstrates the renewal of cultural forms and the transformative power of "small" atomized individuals in reinventing a youthful coalition of silenced, belittled, and marginalized groups. A thoroughly interdisciplinary study, Youth Economy, Crisis, and Reinvention in Twenty-First-Century China will be useful to students and scholars of Chinese culture and society, as well as Literary Studies, Cultural Studies, Gender Studies and Media Studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Youth -- China -- Social conditions -- 21st century; Youth -- China -- Economic conditions -- 21st century; Youth -- China -- Attitudes -- 21st century; SOCIAL SCIENCE / General